Among the Pines; or, South in Secession Time - Gilmore, James R. (James Roberts), 1822-1903 (Salt Lake City, UT : Project Gutenberg, 2007)
"Among the Pines; or, South in Secession Time" by James R. Gilmore is a historical account written in the early 19th century. The work explores the social dynamics of the Southern United States during the tumultuous period of secession. The narrative follows the experiences of the narrator, who journeys into the South and encounters various characters, including Colonel J$1 (B, his servant Jim, and a diverse range of Southern locals, each reflecting the era's complexities surrounding race and the impending Civil War. At the start of the book, the narrator recounts his journey to South Carolina, where he intends to visit Colonel J$1 (B, a plantation owner. He shares his encounter with Jim, the Colonel's intelligent African American servant, and illustrates the stark contrasts of Southern life as he observes the dilapidation of Georgetown and the prevailing attitudes towards secession. Various interactions with locals reveal the tension bred by the political climate, foreshadowing the societal upheaval that the nation is about to face. The opening sets the stage for a deep exploration of Southern social life, racial dynamics, and the impending conflict that looms over the characters involved. (This is an automatically generated summary.)s
Release date is 2007-10-11
E-text prepared by David Garcia, Annie McGuire, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by the Kentuckiana Digital Library (http://kdl.kyvl.org/)
Keywords: War stories; United States -- History -- Civil War, 1861-1865 -- Fiction; Southern States -- History -- Fiction; Confederate States of America -- History -- Fiction